Risk management in the context of innovation projects implementation at machine-building enterprises - Полінський, Олександр Маркович; Ширін, Артем Леонідович (Technology audit and production reserves, 2016)
Methodology to reduce the risks of innovative projects implementation at machine-building enterprises is proposed. Currently analysis methods of the innovation risks are not generalized completely. Methods of negative factors effect on the efficiency of innovative projects should be improved. The uncertainty in the development of innovative projects results in possible losses which quantitative measure is risk. Uncertainty of an event occurrence and its undesirability are required risk components. That is shown in associated expenditures reflecting either direct damage or indirect one. This methodology is based on the rejection of risky innovation project in favour of less risky one or on the risk minimization. The necessity to substantiate at the planning stage the quantitative values of economic indicators when further implementation of the project is not expedient is proved. The research is of practical value for machine-building enterprises as it proposes to develop the concept of an innovation project before its implementation; to analyze and systematize the risks of innovative projects according to certain parameters determined in the research as they are typical for machine-building enterprises. Moreover, five-stage assessment of total innovation risk according to the results of the analysis and systematization is proposed.